Electropulsing Aging Treatment of Cu–Ni–Si Sheet for Microforming. Issue 8 (2nd May 2021) - Zhu, Jie; Lin, Yao; Liu, Shan; Lin, Xudong; Wang, Guangchun
Abstract : Electropulsing aging treatment (EAT) can achieve a significant increase in the strength and conductivity of a Cu–Ni–Si alloy in a short time while maintaining a lower temperature. Compared with aging treatment in a conventional heating furnace at 450 °C for 120 min, EAT can reach or even exceed the same strength and conductivity in only 5 min. The mechanical and electrical properties of samples treated with 630 and 680 A mm −2 current density are prominently improved. After 45 min of treatment with 680 A mm −2 current density, the tensile strength exceeds 600 MPa, and the conductivity reaches 33.45% International Annealed Copper Standard. The main precipitates of the EAT sample is the δ‐Ni2 Si nanoscale strengthening phase, and there is also the β‐Ni3 Si phase in the copper matrix. The strengthening mechanism is the localized Joule heating generated by the electropulsing and the kinetic energy conversion caused by drift electrons, which increases the migration rate of solute atoms Si and Ni and reduces the energy barrier required in the precipitation process, thereby accelerating the formation of precipitates. EAT has the potential to become a new process for the preparation of high‐strength and high‐conductivity copper alloys. Abstract : Electropulsing treatment is proposed to replace the traditional aging treatment; it can achieve a significant increase in the strength and conductivity of a Cu–Ni–Si alloy in a short time while maintaining a lower temperature. Coupled physical effects caused by electropulsing enhance the diffusion ability of solute atoms and reduce the energy barrier.